Molecular Control of the δ-opioid Receptor Signaling and Functional Selectivity by Sodium - Blgacim, Nuria (Université d'Ottawa / University of Ottawa, 2018)
Accumulating evidence suggests a prominent role of the arrestin-dependent signaling pathway in triggering most of the deleterious side effects observed using δ-OR targeting drugs. Numerous small molecules targeting the δ-OR receptors have been developed but their pharmacological properties, including their functional selectivity, have been poorly characterized. The absence of functionally selective opioid drugs, and the lack of knowledge of the pharmacological profile and signaling properties of the δ-OR receptor, limits its therapeutic exploitation. The development of functionally selective modulator toward the canonical G protein pathway could importantly increase the therapeutic potential of this receptor while decreasing its deleterious effects. An approach to fine-tune the functional selectivity of a GPCR is by using allosteric modulators. These allosteric modulators would reduce problems associated with drugs targeting the orthosteric site by not chronically activating the receptor. The overall goal of the proposed research is to study the molecular mechanism by which sodium-channel inhibitors allosterically regulates the delta opioid receptor (δ-OR) signaling and functional selectivity. Additionally, the signaling features of the δ-OR signal transduction triggered by biased receptor activation have been investigated. A combination of approaches, including functional studies, molecular modeling and mutagenesis, were used to study the general mechanism underlying the activation and tuning of the δ-OR signal transduction behavior. Thus, this work suggests the druggability of the allosteric sodium pocket by using sodium channel inhibitors. The current research represent discovery of two different allosteric profiles for the β-arrestin recruitment and one allosteric profile for the G-protein pathway at activated DOR and would serve as scaffold for further refinement of modulators with the desired pharmacological profile.
Keywords: Delta opioid receptor; Sodium cavity; Allosteric modulators